Alevi politics of recognition: transformation of Alevism and two kinds of recognition politics - Aydın, Bengü. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study scrutinizes how the dominant political discourse on religion effects the transformation of Alevism and the Alevi politics of recognition. It attempts to demonstrate the constituents of this dominant political discourse on religion towards Alevism by mainly using the debates sparkled by the AKP’s Alevi Opening in order to present the positions of those holding political power and of the prominent Alevi organizations within the Alevi movement. Although the emergence of Alevi movement beginning from the 1990s has already led to the formalization and standardization of traditional Alevism which we can trace in three examples of core elements of Alevism, cem ceremonies, semahs and dedelik institutiton, certain examples of the reproduction of Alevism have accomodated to a version of Alevism which might be delineated as “acceptable” with respect to the conditions imposed by the dominant discourse on religion. This thesis also examines the two kinds of politics of recognition within the Alevi movement as represented by the Alevi Bektashi Federation and the Alevi Foundations Federation. Besides, these organizations are analyzed in terms of their priorities, self-definition of their institutions, their views about the Alevis’ demands and about the implementation of laicism in Turkey.|Keywords: Alevism, politics of recognition, Alevi Bektashi Federation, Alevi Foundations Federation, AKP, laicism.
Keywords: Bektashi -- Turkey.; Laicism -- Turkey.